Instructional Mnemonic Strategies in Fiqh Learning for Non-Residential Students: Enhancing Memory Retention and Active Learning - Rizqi Avita Khoirun Nisya; Hasyim Asy’ari (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of instructional mnemonic strategies in Islamic jurisprudence (Fiqh) learning for non-residential students and to identify the factors supporting and hindering their implementation. This study employed a qualitative case study approach. Data were collected through in-depth interviews, observations, and documentation involving Fiqh teachers, non-residential students, and program coordinators. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that instructional mnemonic strategies were implemented through abbreviations, acronyms, songs, nadzam (rhythmic verses), rhythmic repetition, flash quizzes, and active recall integrated with the talaqqi learning system. These strategies enhanced students' memory retention, learning motivation, classroom participation, and independent learning skills. Their successful implementation was supported by students' characteristics, a conducive Islamic learning culture, teachers' creativity, and adequate learning facilities. However, differences in students' abilities, limited instructional time, an overreliance on memorization, and insufficient learning supervision outside the classroom remained significant challenges. The study implies that instructional mnemonic strategies offer an innovative and effective pedagogical approach for improving Fiqh learning among non-residential students.